Evaluatıng student's motıvatıon on E-Dıctıon: Masscomm Jargon App. - a case study of UıTM students / Siti Nasarah Ismail...[et al.] - Ismail, Siti Nasarah; Mohd Shukri, Nur Alyani; Ramli, Noryusnita; Abdul Latiff, Dzaa Imma; Manshor, Maizura (2019)
This study provides an overview of using mobile application as a learning aid in assisting students in their learning. E-Diction: Masscomm Jargon App is an electronic dictionary in a form of mobile application that compiles technical terminology, terms of art, known as jargon that has particular meaning within communication field. Students may use this application in order to help them for better understanding about every subject they learn. Therefore, students were given this application as a reference for their learning, followed by this research to evaluate students' motivation in using the E-Diction: Masscomm Jargon App. Moreover, the objective of this study is to identify students' influences and motivation factors of using the e-Diction. A convenience survey is conducted in order to gain feedback from the students about this application. The finding shows the students agreed that this application really help them in their learning process and they may perform well in their study. Furthermore, the using of E-Diction: Masscomm Jargon App has a major contribution to the development of learning as it is reliable to keep and bring anytime and anywhere.